Revisiting the genus Nodularia (Bivalvia, Unionidae): Mitochondrial phylogenomics and the description of a new species - Kaiyu Hou; Xiaoyan Liu; Liping Zhang; Gaiping Li; Ruiwen Wu (Zoosystematics and Evolution)
The genus Nodularia poses a significant challenge to traditional species classification and identification due to its highly convergent and variable shells, rendering it one of the most intricate groups within the family Unionidae. Fortunately, significant progress has been made by researchers in recent years regarding the species validity and the phylogeny of this group based on molecular data. However, the inadequate exploration of regional constraints and inherent limitations in research methodologies remains a crucial factor contributing to the underestimation of species diversity. In this study, a new species of freshwater mussel from the Qingshui River in Nanning City, Guangxi Province, China, Nodularia guiensis sp. nov., is described based on shell morphology, anatomical characters, and molecular phylogenetics. Mitochondrial phylogenomic analyses reveal the following phylogenetic relationships: (((Nodularia hanensis + Nodularia micheloti) + Nodularia dorri) + (Nodularia breviconcha + (Nodularia huana + (Nodularia fusiformans + (Nodularia guiensis sp. nov. + ((Nodularia nuxpersicae + Nodularia nipponensis) + (Nodularia dualobtusus + Nodularia douglasiae))))))). The discovery of this new taxon further enhances the diversity level within the genus Nodularia in China and also highlights the necessity for comprehensive surveys of unexplored regions in order to potentially unveil additional new taxa in the future.